2011
DOI: 10.1097/rlu.0b013e3182291c2a
|View full text |Cite
|
Sign up to set email alerts
|

13N-NH3 Versus F-18 FDG in Detection of Intracranial Meningioma

Abstract: These preliminary results suggest that (13)N-NH(3) has relatively greater uptake in meningiomas in comparison with F-18 FDG. Clinical applications of (13)N-NH(3) PET for grading and follow-up of meningiomas need to be assessed in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
0
27
0
3
Order By: Relevance
“…11C-acetate, another lipid PET tracer, showed high uptake in all 20 meningiomas, in contrast to the low uptake in surrounding normal brain tissue19, whereas with FDG 17 foci appeared photopenic and 3 hyper-intense. 13N-ammonia also had relatively greater uptake in 10 meningiomas when compared with FDG 20. Aminoacid PET tracers are also capable of demonstrating meningiomas: for delineation of gross tumour volume in stereotactic radiotherapy using 11 C-methionine21, or in recurrent cases using 18 F-fluoroethyltyrosine22, or in one patient referred to FDOPA PET for Parkinson’s disease 23.…”
Section: Discussionmentioning
confidence: 99%
“…11C-acetate, another lipid PET tracer, showed high uptake in all 20 meningiomas, in contrast to the low uptake in surrounding normal brain tissue19, whereas with FDG 17 foci appeared photopenic and 3 hyper-intense. 13N-ammonia also had relatively greater uptake in 10 meningiomas when compared with FDG 20. Aminoacid PET tracers are also capable of demonstrating meningiomas: for delineation of gross tumour volume in stereotactic radiotherapy using 11 C-methionine21, or in recurrent cases using 18 F-fluoroethyltyrosine22, or in one patient referred to FDOPA PET for Parkinson’s disease 23.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 2 out of 16 grade II lesions displayed higher uptake of 13 N-ammonia than normal gray matter, one of which also displayed avid uptake of 18 F-FDG and was confirmed with inflammatory infiltration finally (Fig. 14,16 However, most meningiomas have extremely high uptake of 13 Nammonia and very low uptake of 18 F-FDG, while PCNSLs have highest uptake of 18 F-FDG and relatively lower uptake of 13 Nammona. Macrophages are not only avid glucose consumers; they also disrupt the BBB and facilitate the uptake of 13 N-ammonia.…”
Section: Discussionmentioning
confidence: 91%
“…Apart from abnormal metabolic processes, CNS tumors also show increased perfusion, which can be visualized using [ 13 N]ammonia ([ 13 N]NH 3 ). The use of [ 13 N]NH 3 to study cerebral blood flow has been performed in patients with glioma, brain metastases, and meningioma [87][88][89][90][91]. Xiangsong et al showed increased tracer uptake to be present in 95% of MR contrast-enhancing lesions, suggesting BBB dependency [88].…”
Section: Diagnostic Imaging Of Increased Perfusionmentioning
confidence: 99%